Spatial distribution of sewage pollution on a Hawaiian coral reef. (May 2018) - Abaya, Leilani M.; Wiegner, Tracy N.; Beets, James P.; Colbert, Steven L.; Carlson, Kaile'a M.; Kramer, K. Lindsey
Abstract: While sewage pollution is contributing to the global decline of coral reefs, its offshore extent and direct reef impacts from water column mixing and benthic seeps are poorly documented. We addressed this knowledge gap on a Hawaiian coral reef using sewage indicator and benthic cover measurements, macroalgal bioassays, and a pollution scoring tool. Fecal indicator bacteria (FIB) and nutrient concentrations were spatially variable in surface and benthic waters, with shoreline values being highest. Shoreline macroalgae δ 15 N and %N indicated high nitrogen loads containing sewage, while offshore surface and benthic values suggested lower nitrogen loads from environmental sources. Coral cover was negatively correlated with FIB, macroalgal δ 15 N, and nutrient concentrations. Benthic salinity and temperature measurements detected daily tidal groundwater pulses which may explain these associations. While pollution scores revealed that sewage was largely concentrated along the shoreline, results showed some reached the reef and may be contributing to its declining condition. Highlights: Sewage indicators varied spatially in shoreline, surface, and benthic waters. Coral cover was negatively associated with FIB, macroalgal δ 15 N, and nutrients. Daily tidal groundwater pulses exposed reef to sewage. Sewage pollution was higher in shoreline waters than in offshore reef waters.